2020
DOI: 10.1002/ptr.6791
|View full text |Cite
|
Sign up to set email alerts
|

The effect of saffron supplementation on some inflammatory and oxidative markers, leptin, adiponectin, and body composition in patients with nonalcoholic fatty liver disease: A double‐blind randomized clinical trial

Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) is characterized by oxidative stress and inflammation in the hepatocytes. Saffron and its constituents are reported to have several properties such as anti-inflammatory and anti-diabetic effects. Materials and methods: In a randomized double-blind placebo-controlled trial with two parallel groups including 76 eligible men and female patients with NAFLD aged 18-65, recruited from Hazrat Rasul Akram Hospital in Tehran, Iran. NAFLD was defined by a Gastroentero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 35 publications
1
51
0
Order By: Relevance
“…After full text screening, we excluded further 20 studies as they failed to report on variables of interest. Thus, 10 trials met the established criteria to be included in this systematic review and meta‐analysis (Abedimanesh et al., 2020 ; Azimi et al., 2014 ; Ebrahimi et al., 2019 ; Ghaderi et al., 2019 ; Ghiasian et al., 2019 ; Hamidi et al., 2020 ; Karimi‐Nazari et al., 2019 ; Pour et al., 2020 ; Shahbazian et al., 2019 ; Tahvilian et al., 2020 ). The flow diagram of study selection is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After full text screening, we excluded further 20 studies as they failed to report on variables of interest. Thus, 10 trials met the established criteria to be included in this systematic review and meta‐analysis (Abedimanesh et al., 2020 ; Azimi et al., 2014 ; Ebrahimi et al., 2019 ; Ghaderi et al., 2019 ; Ghiasian et al., 2019 ; Hamidi et al., 2020 ; Karimi‐Nazari et al., 2019 ; Pour et al., 2020 ; Shahbazian et al., 2019 ; Tahvilian et al., 2020 ). The flow diagram of study selection is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The age of participants in included trials ranged from 31 to 57 years. The studies enrolled participants with type 2 diabetes (Azimi et al., 2014 ; Ebrahimi et al., 2019 ; Shahbazian et al., 2019 ), coronary artery disease (Abedimanesh et al., 2020 ), ulcerative sclerosis (Tahvilian et al., 2020 ), multiple sclerosis (Ghiasian et al., 2019 ), nonalcoholic fatty liver (Pour et al., 2020 ), rheumatoid arthritis (Hamidi et al., 2020 ), overweight/obese prediabetic patients (Karimi‐Nazari et al., 2019 ), and methadone maintenance treatment patients (Ghaderi et al., 2019 ). In addition, articles were performed on subjects with various baseline body mass index (BMI) values; nine studies (Abedimanesh et al., 2020 ; Azimi et al., 2014 ; Ebrahimi et al., 2019 ; Ghaderi et al., 2019 ; Giannoulaki et al., 2020 ; Hamidi et al., 2020 ; Karimi‐Nazari et al., 2019 ; Milne et al., 2015 ; Pour et al., 2020 ; Shahbazian et al., 2019 ; Tahvilian et al., 2020 ) were conducted on participants with a BMI over 25 kg/m 2 up to 29.9 kg/m 2 , and one study did not report BMI (Ghiasian et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from clinical trials have indicated that saffron Abbreviations: ALT, alanine transaminase; AST, aspartate aminotransferase; BUN, blood urea nitrogen; CAT, catalase; CCT, crocetin; CR, creatinine; DL, druglikeness; DAVID, visualization and Integrated Discovery; GO, Gene ontology; H&E, haematoxylin and eosin staining; HFD, high-fat diet; HO-1, hemeoxygenase-1; IL-1β, interleukin-1β; IL-6, interleukin-6; KEGG, Kyoto Encyclopedia of Genes and Genomes; MDA, malondialdehyde; NAFLD, non-alcoholic fatty liver disease; NAS, NAFLD activity score; Nrf2, nuclear factor erythroid-related factor; OB, oral bioavailability; PPI, protein-protein interaction network; SOD, superoxide dismutase; TC, total cholesterol; TCMSP, traditional Chinese Medicine Systems Pharmacology; TCMID; traditional Chinese Medicine Integrated Database; TG, triglyceride; TNF-α, tumor necrosis factor-α; UA, uric acid. supplementation has beneficial effects on the serum levels of inflammatory, oxidative stress, and adipokines biomarkers in patients with NAFLD (22). Existing research provides evidence on the effect of saffron in the treatment of NAFLD, however, further studies are needed to better elucidate the main bioactive ingredients and signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, recent research demonstrates a hepatoprotective effect of saffron in diabetic rats ( 21 ). Results from clinical trials have indicated that saffron supplementation has beneficial effects on the serum levels of inflammatory, oxidative stress, and adipokines biomarkers in patients with NAFLD ( 22 ). Existing research provides evidence on the effect of saffron in the treatment of NAFLD, however, further studies are needed to better elucidate the main bioactive ingredients and signaling pathways.…”
Section: Introductionmentioning
confidence: 99%